1A.01: MUTATIONS AFFECTING THE CONSERVED ACIDIC MOTIF OF WNK1 CAUSE INHERITED NORMOTENSIVE HYPERKALEMIC ACIDOSIS. (June 2015) - Picard, H. Louis Dit; Thurairajasingam, N.; Decramer, S.; Girerd, X.; Oshaugnessy, K.; Mulatero, P.; Roussey, G.; Tack, I.; Unwin, R.; Vargas-Poussou, R.; Jeunemaitre, X.
Abstract : Objective: Mutations in the WNK1 and WNK4 genes have been shown to cause Familial Hyperkalemic Hypertension (FHHt, OMIM #145260), an inherited disorder combining arterial hypertension and hyperkalemia with metabolic acidosis. More recently, mutations in the KLHL3-CUL3 E3 ubiquitin ligase complex have shed light on the importance of the With-No-Lysine kinases (WNKs) cellular degradation on ion transport. Design and method: Here we identified a new form of autosomal dominant hyperkalemic tubular acidosis with normal blood pressure caused by missense mutations in the WNK1 gene. Using full exome sequencing in a four-generation family and then targeted sequencing in 26 other FHHt cases, we identified six charge-changing substitutions in nine pedigrees. Results: All of them were clustered in a short acidic conserved motif, homolog to that found mutated in the WNK4 protein in FHHt patients. Affected subjects had an early-onset disease and a marked biological phenotype, but surprisingly normal blood pressure values. Comparison with subjects with WNK1 intron 1 deletion or WNK4 mutations showed significant blood pressure differences. Conclusions: In conclusion, we have identified a new type of WNK1 mutations leading to distal tubular hyperkalemic acidosis without tendency for arterial hypertension.